Jawabanmu

2013-12-12T19:59:50+07:00
Pers 1 & 2 ) x + 2y + z = 16      (x 4)
                      3x + y + 4z = 34    (x 1)
4x + 8y + 4z = 64
3x + y + 4z = 34  -
x + 7y = 30  .....(4) 
pers 2 & 3 ) 3x + y +4z = 34      (x 1)
                      2x + 3y + z = 22    (x 4)
3x + y + 4z = 34
8x + 12y + 4z = 88  -
-5x - 11y = -54 .....(5)

pers 4 & 5 )   x + 7y = 30       (x 5)
                       -5x -11y = -54    (x 1)
5x + 35y = 150
-5x -11y = -54  +
        -24y = 96
             y = 4
x + 7(4) = 30 --> x = 2
2 + 2(4) + z = 16 --> z = 6

2013-12-12T23:05:13+07:00
Pers 1 & 2 ) x + 2y + z = 16      (x 4)
                      3x + y + 4z = 34    (x 1)
4x + 8y + 4z = 64
3x + y + 4z = 34  -
x + 7y = 30  .....(4)  
pers 2 & 3 ) 3x + y +4z = 34      (x 1)
                      2x + 3y + z = 22    (x 4)
3x + y + 4z = 34
8x + 12y + 4z = 88  -
-5x - 11y = -54 .....(5)

pers 4 & 5 )   x + 7y = 30       (x 5)
                       -5x -11y = -54    (x 1)
5x + 35y = 150
-5x -11y = -54  +
        -24y = 96
             y = 4
x + 7(4) = 30 --> x = 2
2 + 2(4) + z = 16 --> z = 6